Mechanical Control of Polaritonic States in Lead Halide Perovskite Phonons Strongly Coupled in THz Microcavity - Kim, H. S.; Khan, A. A.; Park, J. Y.; Lee, S.; Ahn, Y. H. (Journal of Physical Chemistry Letters, 2023)
We demonstrate the generation and control of polaritonic states in perovskite phonon polaritons, which are strongly coupled in the middle of a flexible Fabry-Perot cavity. We fabricated flexible perovskite films on a microporous substrate coated with graphene oxide, which led to a virtually free-standing film incorporated into the microcavity. Rabi splitting was observed when the cavity resonance was in tune with that of the phonons. The Rabi splitting energy increased as the film thickness increased, reaching 1.9 meV, which is 2.4-fold higher than the criterion for the strong coupling regime. We obtained dispersion curves for various perovskite film thicknesses exhibiting two polariton branches; clear beats between the two polaritonic branches were observed in the time domain. Flexible cavity devices with perovskite phonons enable macroscopic control over the polaritonic energy states through bending processes, which add an additional degree of freedom in the manipulation of polaritonic devices.
Keywords: Fabry-Perot cavity; Film-thickness; Graphene oxides; Halide perovskites; Mechanical control; Microporous substrate; Perovskite films; Phonon polaritons; Polaritonics; Rabi splitting